Preparation of macromolecular complexes for cryo-electron microscopy - Grassucci, Robert A (2007)
This protocol describes the preparation of frozen-hydrated single-particle specimens of macromolecular complexes. First, it describes how to create a grid surface coated with holey carbon by first inducing holes in a Formvar film to act as a template for the holey carbon that is stable under cryo-electron microscopy (cryo-EM) conditions and is sample-friendly. The protocol then describes the steps required to deposit the homogeneous sample on the grid and to plunge-freeze the grid into liquid ethane at the temperature of liquid nitrogen, so that it is suitable for cryo-EM visualization. It takes 4–5 h to make several hundred holey carbon grids and about 1 h to make the frozen-hydrated grids. The time required for sample purification varies from hours to days, depending on the sample and the specific procedure required. A companion protocol details how to collect cryo-EM data using an FEI Tecnai transmission electron microscope that can subsequently be processed to obtain a three-dimensional reconstruction of the macromolecular complex.